Dengeki daisy. Vol. 6 - Motomi, Kyousuke (Shojo beat manga., 2011)
"Teru and Kurosaki continue to investigate the fake DAISY incident and are on the verge of solving the case when Teru gets kidnapped! What does the kidnapper want with her, and will Kurosaki be able to rescue her in time?!"--Page 4 of cover.